Drug Use Trajectories: Ethnic/Racial Comparisons, 1998-2002 (United-States) - Turner, Jay ([Verlag nicht ermittelbar], 2011)
Drug Use Trajectories is a two-wave panel study of noninstitutionalized young adults from South Florida that was designed to provide epidemiological estimates of drug use in early adulthood. In addition to a structured interview that measures lifetime prevalence of DSM-IV substance use and psychiatric disorders, the study included an extensive battery of measures that assessed lifetime and recent stress exposure, subsyndromal depression and anxiety, social support, and psychosocial risk and protective factors thought to be implicated in their etiology. This community-based epidemiological study was motivated by theoretical linkages between the social system, differential exposure of individuals within the system to social factors that can harm health, and to others that are protective, to explain persistent health disparities at the population level. The study assessed major depression, dysthymia, generalized anxiety disorder, social phobia, panic disorder, alcohol abuse and dependence, drug abuse and dependence, post-traumatic stress disorder, and antisocial personality disorder. Modules from the Diagnostic Interview Schedule (DIS) were included to assess the latter two disorders, and to assess AD/HD. Sub-clinical depression was measured using the Center for Epidemiologic Studies Depression scale (CES-D). The measures of stress exposure in the study involved four dimensions of stressful experience: recent life events, chronic stress, lifetime major and potentially traumatic events, and discrimination stress.